The impact of online word of mouth and social media marketing on purchase intention - Nguyễn Thị Khánh Thảo; Trần Huỳnh Tấn Sang; Lý Phước Sang; Đặng Thanh Tài; Bùi Ngọc Tuấn Anh (Tạp chí Khoa học Đại học Mở Thành phố Hồ Chí Minh - Kinh tế và Quản trị kinh doanh)
Digital technology has become a major driving force in shaping modern commerce, particularly in the realm of online shopping. This study explores the factors influencing the online shopping behavior of students in Ho Chi Minh City, based on the Theory of Planned Behavior (TPB) framework. Utilizing the PLS-SEM method and analyzing data collected from students, the research has revealed that e-WOM (electronic Word-Of-Mouth) and SMM (Social Media Marketing) significantly impact purchase intentions through perceived risk and value. Importantly, the study not only considers the influence of objective factors on subjective ones but also assesses them as a dynamic system, clarifying how these elements interact and simultaneously affect online shopping decisions. Finally, the research provides management strategies for businesses seeking to expand their online operations and proposes potential research directions for the future while also pointing out the current study’s limitations.